An Overview of the Guide Used for Medicolegal Evaluation of Injury Crimes - Aktaş, Ekin Özgür; Kaya, Ahsen (The Bulletin of Legal Medicine, 2017)
Due to their prevalence, injury crimes constitute a substantial part of crimes evaluated medically. Assessment and reporting of the lesions in injured individuals during investigation and adjudication is a significant assignment incurring liability. In this article, in the light of recent developments we present our opinions, critics and suggestions regarding the guide put together with the purpose of securing uniformity between forensic reporting practices.